KONTEN DIGITAL DAN PROMOSI ONLINE MENDORONG MINAT BELI KONSUMEN BOLU AMOR - Ratu Ipmawati, Irfan Hary Purwanto; Ida Farida, Rizky Hilal; Sumiyati, Sendi Permana (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze the influence of digital marketing content and the intensity of online promotion on consumers’ purchase intention toward the local culinary product Bolu Amor. Amid increasingly intense competition in the culinary sector, optimizing digital marketing strategies has become a key factor in attracting consumer attention. The research employs a quantitative approach with descriptive and verificative methods. Data were collected through an online survey of 100 respondents selected using purposive sampling, with criteria limited to consumers exposed to Bolu Amor’s digital activities. Data analysis was conducted using multiple linear regression with SPSS software. The partial results indicate that digital marketing content has a positive and significant effect on purchase intention (t-value = 4.876), as does online promotion intensity (t-value = 3.982). Simultaneously, both variables significantly influence consumers’ purchase intention, as indicated by an F-value of 38.642. The Adjusted R Square value of 0.771 suggests that 77.1% of the variation in purchase intention is explained by digital content and online promotion, while the remainder is influenced by other factors outside the model. These findings confirm that the integration of creative visual content and consistent promotional frequency is crucial in stimulating consumers’ purchase intentions.